Hubungan Adversity Quotient Dengan Kecemasan Menghadapi Dunia Kerja Pada Freshgraduate Universitas Syiah Kuala - T.M. Noor Rachmady; Eka Dian Aprilia (Jurnal Online Psikogenesis, 2018)
Competition in the world of work in the modern era is now more difficult, the phenomenon has an impact on unemployment is increasing every year. This causes anxiety on fresh graduate who just entered the world of work. Known one of the factors that can minimize anxiety in fresh graduate is adversity quotient. This allows fresh graduate to overcome difficulties related to the competition of the work world. The purpose of this research is to find out the relationship between adversity quotients with anxiety to face work world at fresh graduate of Syiah Kuala University. The sampling technique used is incidental sampling. The sample of the study amounted to 257 fresh graduates (120 men and 137 women). Data collection using the Adversity quotient scale compiled by Khairiyah (2016) and the scale of anxiety against the world of work compiled by Nugroho (2010). Data analysis using Pearson correlation technique showed correlation coefficient (r) = -0,598 (p 0,05) so it can be interpreted that there is negative and significant relationship between adversity quotient with anxiety to face work world at fresh graduate of Syiah Kuala University and the hypothesis in this research is accepted.